Global parameter optimization for biokinetic modeling of simple batch experiments. (November 2016) - Mašić, Alma; Udert, Kai M.; Villez, Kris
Abstract: Environmental process modeling is challenged by the lack of high quality data, stochastic variations, and nonlinear behavior. Conventionally, parameter optimization is based on stochastic sampling techniques to deal with the nonlinear behavior of the proposed models. Despite widespread use, such tools cannot guarantee globally optimal parameter estimates. It can be especially difficult in practice to differentiate between lack of algorithm convergence, convergence to a non-global local optimum, and model structure deficits. For this reason, we use a deterministic global optimization algorithm for kinetic model identification and demonstrate it with a model describing a typical batch experiment. A combination of interval arithmetic, reformulations, and relaxations allows globally optimal identification of all (six) model parameters. In addition, the results suggest that further improvements may be obtained by modification of the optimization problem or by proof of the hypothesized pseudo-convex nature of the problem suggested by our results. Graphical abstract: Highlights: Objective function bounds for global biokinetic parameter optimization are proven. Global deterministic parameter estimation of a six-parameter model is possible. Globally optimal parameters are obtained to fit the model to experimental data.